THE EXPERIMENTAL SPECIFYING OF THE DIRECTION OF THE RESULTANTS OF RESISTANCE, INFLUENCING THE SUCKED SEED IN THE VACUUM SOWING APPARATUS - A. NESMIYAN; P. LOBACHEVSKY; V. KHIZHNYAK (Advanced Engineering Research)
The method and the results of the experimental investigation is expounded, which allow to set the direction of the resultants of resistance, influencing the seed, caught by the sucking hole of the vacuum sowing apparatus of the exact drill. The data can be used in theoretical calculation of the parameters and the working regimes of such apparatus.